Weak localization and microwave-irradiated transport in multilayer epitaxial graphene grown on SiC. (3rd November 2015) - Liu, Chieh-I; Wang, Pengjie; Mi, Jian; Lee, Hsin-Yen; Wang, Yi-Ting; Ho, I-Fan; Zhang, Chi; Lin, Xi; Elmquist, Randolph E; Liang, Chi-Te
Abstract: We have studied weak localization (WL) and microwave-irradiated transport in multilayer graphene grown on SiC(0001). Different scattering channels are identified by analyzing the WL data. Moreover, we have shown that at a fixed ambient temperature, irradiating graphene with a microwave appears to be equivalent to changing the ambient temperature without microwave. We find that both the zero-field resistance of graphene and the WL correction term can be used as reliable thermometers which agree well with each other.